Evaluation of stripe rust resistance and analysis of resistance genes in wheat genotypes from Pakistan and Southwest China - Abbas, Sakina; Li, Yunfang; Lu, Jing; Hu, Jianming; Zhang, Xinnuo; Lv, Xue; Shahzad, Armghan; Ao, Donghui; Abbas, Maryam; Wu, Yu; Zhang, Lei; Fayyaz, Muhammad (Frontiers in Plant Science, 2024)
Stripe rust, caused by Puccinia striiformis f. sp. tritici, poses a significant threat to wheat quality and production worldwide, including in China and Pakistan. The rapid evolution of Pst races makes several resistance genes ineffective, which highlight the need for ongoing research to identify new resistance germplasm resources and resistance genes. The current study evaluated stripe rust resistance genes in 349 genotypes from Pakistan and Southwest China. Previously published functional and linked molecular markers were used to detect 13 major stripe rust resistance genes (Yr5, Yr9, Yr10, Yr15, Yr17, Yr18, Yr26, Yr29, Yr30, Yr36, Yr48, Yr65, and YrSp). Field evaluation revealed that over 60% of Chuanyu wheat, 50% of recent Pakistani cultivars, and 20% of historic Pakistani lines were resistant to current stripe rust races. In Chuanyu wheat, Yr17, YrSp, and Yr48 were dominant, though Yr17, Yr26, and YrSp were overused, while Yr36 was absent, and Yr18 was rare. In historic Pakistani lines, Yr5, Yr17, Yr18, and Yr26 were prevalent, while Yr15, Yr26, and YrSp proved effective resistance against current stripe rust races, though Yr29 was absent, and Yr15, Yr30, and Yr48 were overused. Similarly, in recent Pakistani cultivars, Yr15, Yr29, and Yr30 provided effective resistance. A negative correlation between the number of pyramided Yr genes and IT value was found. The study also identified specific Yr gene combinations (Yr26+Yr48, Yr29+Yr5, Yr26+Yr30, and Yr30+Yr17) that enhanced resistance to Pst. These findings outline strategies for the strategic use of genes in breeding for durable resistance in wheat genotypes in Pakistan and Southwest China.